Tracking elderly Alzheimer's patient with radio frequency localization system - Abuhan, Mohd Fadhil (2012)
Humans are sometimes affected by Alzheimer Disease (AD) when aging. AD has major implications on patient safety and care. The elderly Alzheimer’s patient encounters risk of losing all of their memory capability and are unable to live a normal life accordingly. The short memory problem may lead the patients to wander aimlessly and this may lead them to danger. Hence, the Alzheimer’s patients need to be closely monitored to ensure their safety. Some Alzheimer’s patient would be sent by their family to a day care center for day care. The caregivers in day care center have a tough job in monitoring closely the many Alzheimer’s patients at the day care center because of the limited number of caregivers on duty. A motivation of this research is to reduce the caregiver burden. In this research, an assistive technology tools called Alzheimer’s Real Time Location System (ARTLS) was developed to fulfill the research objectives’ of developing Alzheimer’s Real Time Location System (ARTLS) using Active RFID Localization System(AR FIDLS), to understand spatial movement to enhance the monitoring and care management of the residents and lastly to determine the level of suitability of the ARFIDLS in accommodating the AD. The research methodology is implementing ARFIDLS in accommodating the ARTLS functions. The ARTLS is implemented on several Alzheimer’s patients who are residents at the Alzheimer’s day care center. After a successful system implementation on the residents, an analysis on the resident’s visiting area zone and movement sequence pattern percentage is held for determining residents’ daily routine and behavior problems of wandering aimlessly. An analysis of the system performance and system suitability for tracking the Alzheimer patient also been carried out in this thesis. From the research analysis, the residents visiting frequency to each visit area zone is known. it was found also that the residents had a high percentage of movement sequence pattern disagreement. These demonstrate that the residents are wandering aimlessly every day. A suitable selection criteria for radio frequency localization system in accommodating the ARTLS were determined in this thesis. As a general results, ARTLS relieves the caregiver’s burden and enhances residents’ safety by close monitoring of the wandering movements of the residents in real time. Hence, the care for residents will be more efficient and enhanced with better care management practice by the caregiver.